Cost-effectiveness of a nurse-delivered, inpatient smoking cessation intervention. Issue 6 (22nd June 2019) - Ward, Charlotte E; Hall, Stephanie V; Barnett, Paul G; Jordan, Neil; Duffy, Sonia A
Abstract : Health programs in community-based organizations serving racial/ethnic minorities can maximize success by reinforcing organizations' mission and community ties. Abstract: Randomized controlled trials have shown that inpatient tobacco cessation interventions are highly efficacious and cost-effective. However, the degree to which smoking interventions implemented in nonrandomized, real-world practice settings are effective, and consequently, cost-effective, remains unclear. This study evaluated the cost-effectiveness of a nurse-delivered, inpatient smoking cessation intervention, Tobacco Tactics, compared with usual care within the context of an observational, real-world study design. In this quasi-experimental study, five Michigan hospitals ( N = 1, 370 patients) were assigned to implement either Tobacco Tactics or usual care during October 2011–May 2013. Statistical analysis was conducted during January 2017–February 2018. Controlling for confounding using stabilized inverse probability of treatment weights, incremental cost-effectiveness ratios were calculated and cost-effectiveness acceptability curves were generated. The per person cost of tobacco cessation services in the intervention group exceeded that of usual care ($175.52 vs. $67.80; p < .001). The intervention group had a higher propensity-adjusted self-reported quit rate compared to the control group (15.7% vs. 7.0%; p < .0001). The propensity-adjusted incremental cost-effectiveness ratio was $1, 325 per quit (95% confidence interval: $751–$2, 462), with 99.9% probability of being cost-effective at a willingness to pay of $5, 000 per quit. The Tobacco Tactics intervention was found to be cost-effective and well within the range of incremental cost-per-quit findings from other studies of tobacco cessation interventions, which range from $918 to $23, 200, adjusted for inflation.